Thermography in Occlusive Cerebrovascular Diseases. Issue 5617 (31st August 1968) - Mawdsley, C.; Samuel, E.; Sumerling, M. D.; Young, G. B.
Abstract : Cooling of the skin over the medial supraorbital region in 80% of patients who have an occlusion or severe stenosis of a carotid artery can be demonstrated by facial thermography. Minor stenotic lesions in the carotid arteries do not produce characteristic thermographic changes, while thermography is of no help in the diagnosis of vertebrobasilar arterial disease. Thermographic changes suggestive of carotid arterial lesions are found occasionally in patients whose angiograms are normal, owing to variations in the size of the frontal sinuses, or factors such as fever or inflammatory lesions. It is suggested that facial thermography is of value in the preliminary investigation of patients with occlusive cerebrovascular disease.